Downregulation of serotonin reuptake transporter gene expression in healing colonic mucosa in presence of remaining low‐grade inflammation in ulcerative colitis. Issue 8 (August 2016) - Tada, Yasumasa; Ishihara, Shunji; Kawashima, Kousaku; Fukuba, Nobuhiko; Sonoyama, Hiroki; Kusunoki, Ryusaku; Oka, Akihiko; Mishima, Yoshiyuki; Oshima, Naoki; Moriyama, Ichiro; Yuki, Takafumi; Ishikawa, Noriyoshi; et al.
Abstract: Background and Aim: The serotonin reuptake transporter (SERT) terminates serotonin activity by removing it from interstitial space. Downregulated colonic SERT expression has been reported in irritable bowel disease (IBS), and symptoms resembling IBS occur in cases of inflammatory bowel disease (IBD) in remission; thus, a common pathogenesis for IBS and IBD is possible. However, little is known regarding SERT expression in colonic mucosa of IBD patients during healing. Methods: Twenty‐two ulcerative colitis (UC) patients underwent colonoscopy examinations, during which inflamed mucosa was distinguished from that undergoing healing. Healing mucosa was classified into regular and irregular vessel patterns by narrowband imaging magnifying colonoscopy. Expressions of SERT and various inflammation‐related genes in biopsy samples were assessed using a polymerase chain reaction array system and real‐time polymerase chain reaction. Colitis model mice were established by administration of dextran sodium sulfate or transfer of CD4 + T cells isolated from SAMP1 mice, then time‐course changes of SERT and inflammatory gene expressions were observed in colonic mucosa. Results: In UC patients, SERT expression in inflamed mucosa was significantly lower than in healing mucosa. SERT expression was decreased in healing mucosa with an irregular vessel pattern with mildly increased levels of inflammatory gene expression. In mice, SERT expression was suppressed in inflamed mucosa and continuously observed with low‐grade mucosal inflammation during colitis healing. Conclusions: Sserotonin reuptake transporter expression is downregulated in healing colonic mucosa of UC patients and that suppression may be dependent on the presence of remaining low‐grade colonic inflammation.